Heterogeneous photocatalysis of triclocarban and triclosan in greywater: a systematic and bibliometric review analysis - Arifin, Siti nor Hidayah; Mohamed, Radin; Al-Gheethi, Adel; Wei Lai, Chin; Yashn, G. (Taylor&francis, 2023)
In this article, a review for utilising titanium dioxide (TiO2) nanotubes in the photocatalytic degradation of triclocarban (TCC) and triclosan (TCS) in greywater is discussed. The photocatalytic degradation process is widely used to remove pharmaceutical and personal care products (PPCPs) such as TCC and TCS, which are among persistent compounds that gave negative impacts to the environment and human health within the toxicology level of the TCC and TCS are 0.05 mg/L to 2 mg/L and 0.01 mg/L and 0.5 mg/L. Both TCC and TCS are used in the manufacturing of PPCPs. The removal of PPCPs from domestic greywater through chemical and physical processes has been addressed by many researchers. Currently, the photocatalysis by using TiO2 nanotubes is becoming more common for the removal of PPCPs from wastewater. The current review aims to organise the scattered available information on the potential of photocatalytic degradation application for TCC and TCS removal. The topic discussed in the review shows that TiO2 nanotubes has high potential as the catalyst for photocatalytic degradation of TCC and TCS in greywater with the degradation rate are 33% to 99% for TCC and 1.73% to 90% for TCS. Other than that, photocatalytic degradation applied in TCC and TCS removal has led to several nonhazardous photoproducts production due to the reaction occurred.